Critical review of the management of primary central nervous nongerminomatous germ cell tumors. Issue 6 (15th February 2019) - Abu Arja, Mohammad H.; Bouffet, Eric; Finlay, Jonathan L.; AbdelBaki, Mohamed S.
Abstract: Multimodal strategies have significantly improved the outcomes for patients with central nervous system nongerminomatous germ cell tumors. Two large cooperative group studies have recently reported much improved outcomes compared with historical series. However, a substantial proportion of patients still attain inadequate responses to initial chemotherapy prior to irradiation, with adverse impact upon survival; optimal induction chemotherapy regimens and radiotherapy strategies are as yet unidentified. Outcomes for patients with relapsed disease remain poor. There is an obvious need to incorporate molecular studies within prospective clinical trials that will likely lead to the incorporation of targeted, more effective future treatment strategies.